2019
DOI: 10.1108/ijlls-08-2019-0060
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing the implementation of Lesson Study in Kazakhstan within a social theory framework

Abstract: Purpose The purpose of this paper is to provide an analysis of processes in operation during the implementation of a reform programme in Kazakhstan culminating in the widespread adoption of Lesson Study (LS). Design/methodology/approach The study is positioned within a critical realist theoretical perspective, drawing on Archer’s social theory to focus on the social world of the school while changes to classroom practice are being made. This is a case study using process tracing methods to analyse how school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…By doing so, Kazakhstan's young people will become global learners in the 21st century. A network of professional development centers will provide leadership throughout Kazakhstan to facilitate the development process (Wilson et al, 2013). As originally planned, 70,000 teachers would go through the program each year, and by the beginning of the 2016-2017 school year, all teachers (325,184 in 2016) would complete both levels.…”
Section: Cpd At National Education Reformsmentioning
confidence: 99%
See 1 more Smart Citation
“…By doing so, Kazakhstan's young people will become global learners in the 21st century. A network of professional development centers will provide leadership throughout Kazakhstan to facilitate the development process (Wilson et al, 2013). As originally planned, 70,000 teachers would go through the program each year, and by the beginning of the 2016-2017 school year, all teachers (325,184 in 2016) would complete both levels.…”
Section: Cpd At National Education Reformsmentioning
confidence: 99%
“…Due to the significant gap between urban and rural areas, financial incentives are promised and should be paid from local budgets, but in practice, payments may be delayed or even canceled. Consequently, CPD "Orleu" have started 3-week intensive courses to prepare teachers for the introduction of new educational content since May 2016 due to the inability to achieve the goal of an initial plan (Wilson et al, 2013). In Kazakhstan in 2018-2019, more than 90% of teachers had a degree from a college or university (see Table 1).…”
Section: Cpd At National Education Reformsmentioning
confidence: 99%
“…Other studies have shown that implementing LS improves students' culture, practice, beliefs, expectations and learning (Dudley et al , 2019). Moreover, Wilson and Sharimova (2019), after carrying out a pilot study in Kazakhstan based on improving the education system by implementing LS, concluded that this methodology provided participants with the opportunity to think and make collaborative judgements which had a real effect on teaching practice. These authors state that practice can only be changed by reflecting on what happens in the classroom, and in having both the skills and the time needed to analyse the effect that learning has on pupils.…”
Section: Theoretical Framework and Research Questionsmentioning
confidence: 99%